Iris Freckles - Suman Grover; Nitin Kumar; Srishti Raj (Delhi Journal of Ophthalmology)
A middle-aged Indian female presented to us for a routine eye check-up. The examination revealed the presence of flat, discrete, small, and brownish lesions involving the superficial layers of the iris. There was a significant history of exposure to the sunlight. A diagnosis of iris freckles was considered. This benign entity needs to be differentiated from other serious melanocytic proliferations; however, observation and monitoring of the lesion are recommended.